Thiol Modification of Psyllium Husk Mucilage and Evaluation of Its Mucoadhesive Applications - Meenakshi Bhatia; Munish Ahuja (The Scientific World Journal, 2013)
Thiol functionalization of psyllium was carried out to enhance its mucoadhesive potential. Thiolation of psyllium was achieved by esterification with thioglycolic acid. Thiolation was observed to change the surface morphology of psyllium from fibrous to granular and result in a slight increase in the crystallinity and swelling. Thiolated psyllium was found to contain 3.282 m moles of thiol groups/g of the polymer. Mucoadhesive applications of thiolated psylium were explored by formulating gels using metronidazole as the model drug. On comparative evaluation thiolated psyllium gels showed 3-fold higher mucoadhesive strength than the psyllium gels as determined by modified physical balance using chicken buccal pouch. The results of in vitro release study revealed that thiolated psyllium gels provided a prolonged release of metronidazole. Further, the psyllium and thiolated psyllium gels were found to release the drug following first-order kinetics by combination of polymer relaxation and diffusion through the matrix.